2013
DOI: 10.1007/s00228-013-1479-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of non-warfarin-associated bleeding events reported to the Norwegian spontaneous reporting system

Abstract: Non-warfarin-associated bleeding events are associated with substantial mortality. Old age, cerebral bleeds, number of drugs used, and use of fibrinolytics are all independently associated with increased mortality. The recognition of the bleeding risk of commonly used drugs such as acetylsalicylic acid and heparins may be insufficient among prescribers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Mortality is around 30–50% [7,6062] and severe physical and psychological disablement are possible in those who survive. [17] It would therefore seem to be reasonable to include all cerebral bleeds, fatal and non-fatal, in an evaluation of the risk-benefit balance of aspirin prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality is around 30–50% [7,6062] and severe physical and psychological disablement are possible in those who survive. [17] It would therefore seem to be reasonable to include all cerebral bleeds, fatal and non-fatal, in an evaluation of the risk-benefit balance of aspirin prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Cessation of cigarette smoking after an ischemic stroke is associated with decreased 5-year risk of stroke, myocardial infarction or death [18]. According to Gerner et al [13] and Narum et al [17], the use of NOAC and NSAID is associated with increased risk of intracerebral hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…The increased risk of CVD related to NSAIDs (nonsteroidal anti-inflammatory drugs) [17] and to smoking [18] was estimated using ICF categories e1101, drugs and e1109, products or substances for personal consumption, respectively. The following criteria were used: qualifier 0-NO; qualifier 4-YES.…”
Section: Icf Profilementioning
confidence: 99%
See 1 more Smart Citation
“…Based on analyses carried out by experts of the World Health Organization (WHO), it can be concluded that about 80% of recurrent CVD incidents could be avoided if the most relevant risk factors were eliminated [ 5 ]. The generally recognised modifiable risk factors for CVD related to secondary prevention include arterial hypertension, atrial fibrillation, diabetes, dyslipidaemia, abnormal body mass index (BMI), carotid artery disease, depression, insomnia, smoking, and alcohol abuse [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. The coexistence of the above risk factors increases the likelihood of a recurrent CVD incident [ 21 ]; therefore, it is reasonable to monitor patients for all these risk factors simultaneously.…”
Section: Introductionmentioning
confidence: 99%